Long-term mentoring relationships in undergraduate longitudinal general practice tracks – a qualitative study on the perspective of students and general practitioners. Issue 1 (31st December 2023) - Scholz, Anna; Gehres, Vera; Schrimpf, Anne; Bleckwenn, Markus; Deutsch, Tobias; Geier, Anne-Kathrin
ABSTRACT: Background: Longitudinal general practice tracks have been established in medical faculties in Europe and worldwide to attract more graduates to general practice careers. In many programs, long-term mentoring relationships play an important role in providing students with positive role models, regular practical experiences, and acquisition of clinical skills in a community context. However, little is known about students' and general practitioner mentors' expectations, experiences, challenges, and ideas for improvement within these long-term mentoring relationships in general practice in our medical education system. Methods: Qualitative study based on semi-structured interviews with 15 students and 13 mentors. Interviews were audio-recorded and transcribed verbatim. MAXQDA was used for data analysis, following a mixed deductive/inductive approach. Results: Both groups had few and rather unstated expectations, particularly regarding their relationships. Consequently, expectations were often not clearly communicated. Nevertheless, a high level of satisfaction and good opportunities for teaching were achieved for both sides. The evolving familiarity facilitated a positive learning environment. Students valued independent medical tasks continuously adjusted to their current abilities. However, some felt a reluctance to demand their mentor's time and consideration. Conversely, the mentors criticized a lack of initiative from some of the students and wished that they would get more actively involved. Students, in contrast, wished for more guidance at the start of the project and joint events to deepen the relationship. Conclusions: With this study, we gained detailed insights into and understanding of the nature of long-term relationships between students and mentors. Points for improvement revealed included: 1) education of both participating groups on the goals and benefits of mentoring, including binding expectations for the participants; 2) intensified support and training of teaching physicians; 3) structured and accompanied establishment of initial contact between mentor and mentee; and 4) encouraged additional shared (teaching) time, individualized timing, and intensification, if desired.